The Effect of Internal Supply Chain Management Practices on the Operational Performance of Technical Universities in Ghana - Bright Junior Tanzubil; Oswald Atiga (International Journal of Supply Chain Management, 2022)
This study sought to establish the effect of internal supply chain management practices on the operational performance of tertiary educational institutions in Ghana, particularly the Bolgatanga Technical University in the Upper East Region. The study employed descriptive and inferential research design methods. A survey was conducted using an interviewer-administered questionnaire containing five- point Likert scale test items. Survey data was collected from two hundred and three continuing students of the Bolgatanga Technical University. The data entry software Census and Survey Processing System (CSPro) was used for the data entry and subsequently exported into Statistical Package for Social Sciences (SPSS) for analysis. Data analysis and interpretation was based on descriptive and inferential statistics using multiple regression analysis. Exploratory factor analysis (EFA) was deployed as a construct validation tool. The study's findings revealed that educational internal supply chain practices such as academic training, classroom setting/environment, and non-academic activities (sports and recreation) were significant, whereas the source of admission information, examination, infrastructure, and alumnae activities were not. Since data was collected from continuing students of only the Bolgatanga technical university, it is suggested that a similar study be replicated to include more technical universities and to include all levels of students. The novelty of this research is that supply chain performance is generally assessed from a managerial perspective, but in this study, the operational performance of technical universities is evaluated from a customer (student) perspective.